1999
DOI: 10.1089/ten.1999.5.545
|View full text |Cite
|
Sign up to set email alerts
|

Engineering of Osteochondral Tissue with Bone Marrow Mesenchymal Progenitor Cells in a Derivatized Hyaluronan-Gelatin Composite Sponge

Abstract: The aim of this study was to investigate the potential of a composite matrix, containing esterified hyaluronic acid and gelatin, to facilitate the osteochondral differentiation of culture-expanded, bone marrow-derived mesenchymal progenitor cells. The cell loading characteristics and the effects of the matrix on cell differentiation were examined in vitro and in vivo. Empty and cell-loaded composites were cultivated for up to 28 days in a chemically defined medium with or without transforming growth factor-bet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
144
0
6

Year Published

2001
2001
2017
2017

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 176 publications
(153 citation statements)
references
References 19 publications
3
144
0
6
Order By: Relevance
“…The results show that even though there is a clear deficit of MSC in a BONE MARROW-DERIVED CELL CONCENTRATES USED FOR OSTEOCHONDRAL RECONSTRUCTION 9 Tissue Engineering Part C: Methods bone marrow aspirate concentrate, there is no increasing effect of isolating and proliferating MSC on the bone formation and vascularization of the constructs. The role of MSCs for the regeneration of cartilage is a matter of debate: MSC play a key role during fracture healing, 40 and a transition of MSC into chondrocytes can be achieved both in-vitro 41 and in-vivo. 42 Small molecules such as CBFb, TGFb, IGF1, KGN, and more have been identified to trigger chondrocyte-specific gene expression in MSC and to protect chondrocytes in-vitro.…”
Section: Discussionmentioning
confidence: 99%
“…The results show that even though there is a clear deficit of MSC in a BONE MARROW-DERIVED CELL CONCENTRATES USED FOR OSTEOCHONDRAL RECONSTRUCTION 9 Tissue Engineering Part C: Methods bone marrow aspirate concentrate, there is no increasing effect of isolating and proliferating MSC on the bone formation and vascularization of the constructs. The role of MSCs for the regeneration of cartilage is a matter of debate: MSC play a key role during fracture healing, 40 and a transition of MSC into chondrocytes can be achieved both in-vitro 41 and in-vivo. 42 Small molecules such as CBFb, TGFb, IGF1, KGN, and more have been identified to trigger chondrocyte-specific gene expression in MSC and to protect chondrocytes in-vitro.…”
Section: Discussionmentioning
confidence: 99%
“…For this purpose various animal models were employed to investigate experimental defect healing. The smallest animals used were mice 6 and rats, 7 being followed by rabbits. 8 For more advanced preclinical studies, large animal models such as dogs, 9 goats, 10 pigs 11 or horses 12 were used.…”
mentioning
confidence: 99%
“…Hyaluronic acid (HA) is one of glycosaminoglycans in extracellular matrix and plays important roles in maintaining morphologic organization by preserving extracellular spaces, and has been reported to have excellent potential for tissue engineering [85][86][87][88][89]. It was reported that HA shows important roles in some biological processes, including inhibition of inflammation and pain, and differentiation of osteoblastic and osteoclastic cells [90][91][92].…”
Section: Hyaluronic Acid Sponge For Dental Pulpmentioning
confidence: 99%